2022
DOI: 10.1039/d1tc05526g
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal-free visible-to-UV photon upconversion with over 20% efficiency sensitized by a ketocoumarin derivative

Abstract: Efficient triplet-triplet annihilation-based photon upconversion (TTA-UC) from visible to UV light without using heavy metals is still a challenging task. Here we achieve a record-high TTA-UC efficiency of 20.3% among...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
1
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(53 citation statements)
references
References 45 publications
(76 reference statements)
3
47
1
2
Order By: Relevance
“…In the linear regime, the quantum efficiency is stabilized and has an average value of 12.2 ± 0.8% (Φ′ UC ; normalized to 100%) . This efficiency is slightly higher than the previous record of visible-to-UV upconversion sensitized with perovskite NCs, although it still lags behind the efficiencies achieved with molecular sensitizers. , …”
mentioning
confidence: 73%
“…In the linear regime, the quantum efficiency is stabilized and has an average value of 12.2 ± 0.8% (Φ′ UC ; normalized to 100%) . This efficiency is slightly higher than the previous record of visible-to-UV upconversion sensitized with perovskite NCs, although it still lags behind the efficiencies achieved with molecular sensitizers. , …”
mentioning
confidence: 73%
“…This could potentially explain why we see a higher external Φ UC (13.1%) than that in other studies using TIPS-Naph (Φ UC ≈ 10%), in which Φ TET is reported to be close to unity. 28 , 29 …”
Section: Resultsmentioning
confidence: 99%
“… 30 The 10% limit has also been surpassed by pairing an iridium complex or a ketocoumarin derivative with 1,4-bis((triisopropylsilyl)ethynyl)naphthalene (TIPS-Naph), systems which also demonstrate low threshold excitation intensities ( I th ). 28 , 29 Other annihilators previously investigated include other naphthalene and oxazole derivatives, 8 , 30 , 36 species from the terphenyl family, 13 , 37 and as of recently also a biphenyl derivative with the capability to emit light beyond 4 eV. 38 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TA spectroscopy TA spectra were measured by the pump-probe method [20][21][22]. For a probe pulse, we generated a white light pulse by focusing the signal light (1200 nm) from another OPA (Light Conversion, TOPAS-Prime) on a sapphire crystal (3 mm thickness).…”
Section: Steady-state Pl Spectroscopymentioning
confidence: 99%